The ratio of ADSCs to HSC‐progenitors in adipose tissue derived SVF may provide the key to predict the outcome of stem‐cell therapy. Issue 1 (7th February 2018) - Kilinc, Mehmet Okyay; Santidrian, Antonio; Minev, Ivelina; Toth, Robert; Draganov, Dobrin; Nguyen, Duong; Lander, Elliot; Berman, Mark; Minev, Boris; Szalay, Aladar A.
Abstract: Background: Stromal vascular fraction (SVF) represents an attractive source of adult stem cells and progenitors, holding great promise for numerous cell therapy approaches. In 2017, it was reported that 1524 patients received autologous SVF following the enzymatic digestion of liposuction fat. The treatment was safe and effective and patients showed significant clinical improvement. In a collaborative study, we analyzed SVF obtained from 58 patients having degenerative, inflammatory, autoimmune diseases, and advanced stage cancer. Results: Flow analysis showed that freshly isolated SVF was very heterogeneous and harbored four major subsets specific to adipose tissue; CD34 high CD45 − CD31 − CD146 − adipose‐derived stromal/stem cells (ADSCs), CD34 low CD45 + CD206 + CD31 − CD146 − hematopoietic stem cell‐progenitors (HSC‐progenitors), CD34 high CD45 − CD31 + CD146 + adipose tissue‐endothelial cells and CD45 − CD34 − CD31 − CD146 + pericytes. Culturing and expanding of SVF revealed a homogenous population lacking hematopoietic lineage markers CD45 and CD34, but were positive for CD90, CD73, CD105, and CD44. Flow cytometry sorting of viable individual subpopulations revealed that ADSCs had the capacity to grow in adherent culture. The identity of the expanded cells as mesenchymal stem cells (MSCs) was further confirmed based on their differentiation into adipogenic and osteogenic lineages. To identify the potential factors, which may determine the beneficial outcome of treatment, we followed 44 patients post‐SVF treatment. The gender, age, clinical condition, certain SVF‐dose and route of injection, did not play a role on the clinical outcome. Interestingly, SVF yield seemed to be affected by patient's characteristic to various extents. Furthermore, the therapy with adipose‐derived and expanded‐mesenchymal stem cells (ADE‐MSCs) on a limited number of patients, did not suggest increased efficacies compared to SVF treatment. Therefore, we tested the hypothesis that a certain combination, rather than individual subset of cells may play a role in determining the treatment efficacy and found that the combination of ADSCs to HSC‐progenitor cells can be correlated with overall treatment efficacy. Conclusions: We found that a 2:1 ratio of ADSCs to HSC‐progenitors seems to be the key for a successful cell therapy. These findings open the way to future rational design of new treatment regimens for individuals by adjusting the cell ratio before the treatment.